2022
DOI: 10.1126/scitranslmed.abp8309
|View full text |Cite
|
Sign up to set email alerts
|

CD47-SIRPα axis blockade in NASH promotes necroptotic hepatocyte clearance by liver macrophages and decreases hepatic fibrosis

Abstract: Necroptosis contributes to hepatocyte death in nonalcoholic steatohepatitis (NASH), but the fate and roles of necroptotic hepatocytes (necHCs) in NASH remain unknown. We show here that the accumulation of necHCs in human and mouse NASH liver is associated with an up-regulation of the “don’t-eat-me” ligand CD47 on necHCs, but not on apoptotic hepatocytes, and an increase in the CD47 receptor SIRPα on liver macrophages, consistent with impaired macrophage-mediated clearance of necHCs. In vitro, necHC clearance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 77 publications
1
38
0
Order By: Relevance
“…(figure 6). Overall, we suggest that erythrocyte dysfunction is a substantial aspect of metabolic inflammation as already evidenced by previous studies [6,8,23,32] Our results explain the reported anemia in animal models of NASH, where CD47 targeting had a therapeutic potential on NASH [33,34]; since erythrocytes of NASH patients and animal models exhibit reduced CD47 levels and increased pro-phagocytic signals, targeting of CD47 on erythrocytes enhances their phagocytosis. In addition, our results could also explain the negative impact of the chronic CD47 targeting in NASH animal models [35]; erythrophagocytosis would lead to hepatic dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…(figure 6). Overall, we suggest that erythrocyte dysfunction is a substantial aspect of metabolic inflammation as already evidenced by previous studies [6,8,23,32] Our results explain the reported anemia in animal models of NASH, where CD47 targeting had a therapeutic potential on NASH [33,34]; since erythrocytes of NASH patients and animal models exhibit reduced CD47 levels and increased pro-phagocytic signals, targeting of CD47 on erythrocytes enhances their phagocytosis. In addition, our results could also explain the negative impact of the chronic CD47 targeting in NASH animal models [35]; erythrophagocytosis would lead to hepatic dysfunction.…”
Section: Discussionsupporting
confidence: 86%
“…39 Actually, necroptosis has been shown to have a role in the pathogenesis of a number of liver diseases, including alcoholic liver disease, nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, and toxic hepatitis. [40][41][42] Well in line, it is proved that VPA treatment increases RIPK1 expressions and increases RIPK3 and MLKL levels and enhancing their mRNA gene expression in liver. Excessive ROS production is an imminent driving force for the execution of necroptosis owing to forming more necrosome.…”
Section: Discussionmentioning
confidence: 89%
“…Actually, necroptosis has been shown to have a role in the pathogenesis of a number of liver diseases, including alcoholic liver disease, nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, and toxic hepatitis 40–42 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, liver macrophages increase their expression of the CD47 receptor, SIRPα, leading to impaired clearance of these necroptotic hepatocytes. This was reversed using anti-CD47 or anti-SIRPα treatment in mouse models of NASH, which increased the uptake of these necroptotic hepatocytes by liver macrophages ( Shi et al, 2022 ).…”
Section: Non-alcoholic Fatty Liver Disease (Nafld) and Non-alcoholic ...mentioning
confidence: 99%